2013
DOI: 10.1007/s10198-013-0490-3
|View full text |Cite
|
Sign up to set email alerts
|

Explaining variations in breast cancer screening across European countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…Very similar age trajectories can be observed for each cohort, suggesting no 'true' age effects. The cross-national comparative approach aids in framing these period effects within the context of national screening policies, which have already been empirically linked to the large country-differences in mammography screening (Wübker 2014), illustrated in Fig. 6.4.…”
Section: Principle 2: Timing Of Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Very similar age trajectories can be observed for each cohort, suggesting no 'true' age effects. The cross-national comparative approach aids in framing these period effects within the context of national screening policies, which have already been empirically linked to the large country-differences in mammography screening (Wübker 2014), illustrated in Fig. 6.4.…”
Section: Principle 2: Timing Of Outcomesmentioning
confidence: 99%
“…However, the existing studies have already revealed substantial cross-national variation in preventive health care habits, including mammography screening (e.g. Wübker 2014). An important question now relates to which institutional differences are the driving forces behind this cross-national variation (Blane et al 2007).…”
Section: Principle 5: Principle Of Time and Placementioning
confidence: 99%
See 1 more Smart Citation
“…Health information plays an important role in such decision, affecting the consumers' perceived marginal benefits of health care (Kenkel, 1990). In our specific case, empirical evidence suggests that women tend to have false perceptions of the risks and seriousness of breast cancer (Wuebker, 2013) and this may reduce dramatically their incentive to demand a mammography. However, identifying the impact of information on preventive decisions is complicated because unobserved individual characteristics affect both the decision to do a mammography and the individual efforts to acquire information.…”
Section: Introductionmentioning
confidence: 98%
“…Underuse of preventive care is a large concern for European countries. On average, only 50 per cent of women get an appropriate mammography in Europe, besides, many other countries exhibit sensibly lower rates and high intra-country variation (Carrieri and Wuebker, 2013;Wuebker, 2013). While screening programs are often indicated as a good strategy to increase preventive care use (i.e.…”
Section: Introductionmentioning
confidence: 99%